The Two Governments and the Two Kingdoms in Luther's Thought - Stephenson, John R. (Scottish journal of theology, 1981)
The facet of his thought commonly referred to as the doctrine of the two kingdoms has provoked some of the most intractable confusion and bitter controversy in post-war continental Luther scholarship, and the ripples of this debate which reached these shores have all too often amounted to a litany of sweeping statements which have done nothing to enhance the Reformer's reputation in England. Yet even before Hitler's war Luther had endured a century of disfavour among the leading academic and ecclesiastical circles on this side of the Channel. So marked was British — more particularly, English — distaste for Luther in the opening years of this century that the American church historian Preserved Smith devoted an article to the subject in 1917, listing Anglo-Catholicism, rationalism, socialism and — since 1914 — visceral hostility to all things German as four factors which had conspired to tarnish the Reformer's image in the minds of the English of that time. Fifteen years later the celebrated Modernist H. D. A. Major was to lament that, ‘Today Martin Luther, the greatest protagonist of the Reformation, is viewed as a vulgar, violent and mistaken man as hostile to humanist culture as he was to social democracy.’ The European conflict of the next decade provided the cue for the most damaging slur of all on the Reformer's memory, so that when in 1945 a third-rate pamphleteer denigrated Luther as ‘Hitler's spiritual ancestor’ his thesis had already been expressed by Archbishop William Temple, who had died the previous year.